Evaluation of satisfaction with nursing care in the Children's Surgery Department - Edyta Laska; Anna Cepuchowicz (University of Applied Sciences in Tarnow, Poland, 2021)
Aim: The aim of the study is to assess the satisfaction of parents with nursing care at a pediatric surgery department. Material and method: The research was conducted among parents / caregivers of children discharged from the ward in the period from February to April 2019. The study involved 50 respondents. The test method was a diagnostic poll method in the form of a questionnaire. The research tool was a questionnaire of own authorship. Results: Factors determining satisfaction with child care on a surgical ward are: the age of the child, the mode of the child's admission to the ward, accessibility, and the nurse's support. Thirty-one parents were in favour of the multi-purpose nature of nursing care on the ward. The others felt that nursing care was task-oriented. Parents of the youngest children (mean age 4.9 years) expected the nurse to be kind or professional (mean age 5.5 years). Parents of early childhood children (mean age 7.2 years) were more likely to expect understanding, and parents of the oldest children (mean age 9.0 years) expected communicativeness. It was shown that throughout the entire period of hospitalization, caregivers of children under 3 years of age (n = 13; 100.0%) or aged 3-6 years (n = 15; 78.9%) stayed with their children more often. There was a correlation between the mode of admission and the emotions that parents felt during the admission of their child to hospital, as shown in Tab. 5. The level of significance (p < 0.001) in the hypothesis tested, was lower than the typical level of significance of 0.05. In the case of emergency admission (n = 13; 54%) and planned admission for surgery (n = 17; 74%), emotions related to helplessness and anxiety predominated. Conclusion: Parents rated the quality of nursing care on the ward well. Parents' expectations of the nurse are not dependent on the age of the child. The mode of admission of the child to the ward did not affect the expectations towards the nurse. The age of the child affected the time the caregiver stayed with the child on the ward. The mode of admission of the child affected the emotional state of the parents of the caregivers.